Noble-Metal-Free NiS/C3N4 for Efficient Photocatalytic Hydrogen Evolution from Water - Hong, Jindui; Wang, Yongsheng; Wang, Yabo; Zhang, Wei; Xu, Rong (ChemSusChem, 2013)
A NiS/C3N4 photocatalyst containing earth‐abundant elements only was constructed by means of a simple hydrothermal method. This photocatalyst shows efficient hydrogen evolution (48.2 μmol h−1) under visible light when using triethanolamine as a sacrificial reagent. The optimal loading of 1.1 wt % NiS on C3N4 as a cocatalyst can enhance the H2 production by about 250 times compared with the native C3N4. The highest apparent quantum efficiency of 1.9 % was recorded at 440 nm. The fall of the nobility: Noble‐metal‐free NiS/C3N4 was synthesized by means of a simple hydrothermal method. A small percentage of NiS loading enhances H2 evolution compared to the native C3N4. In addition, a higher apparent quantum efficiency is recorded. The appropriate loading of NiS makes C3N4 a stable and low‐cost photocatalyst system for H2 evolution.